PELATIHAN SEKOLAH SEHAT BAGI GURU DI TK ISLAM DARUNNAJAH - Dwi Puji Lestari (Jurnal Pengabdian Masyarakat (Bisma), 2024)
Healthy school training for teachers at Darunnajah Islamic Kindergarten is a strategic effort to improve the quality of a healthy, safe, and comfortable learning environment for early childhood. Teachers have an important role in instilling healthy living habits and creating a school environment that supports children's physical, mental, and social development. This training aims to provide insight to teachers about the importance of healthy schools as well as concrete steps in realizing them. The training method includes lectures, discussions and questions and answers, simulations, and evaluations. The results of the training showed that teachers experienced an increase in understanding in implementing the concept of healthy schools in schools. With this training, it is hoped that a sustainable healthy school culture will be created, so that children can grow and develop optimally in an environment that supports their welfare